1995
DOI: 10.1152/ajpheart.1995.268.4.h1531
|View full text |Cite
|
Sign up to set email alerts
|

Protection of reoxygenated cardiomyocytes against hypercontracture by inhibition of Na+/H+ exchange

Abstract: Effects of Na+/H+ exchange inhibition and cytosolic acidosis on reoxygenated adult rat ventricular cardiomyocytes were investigated. Cells were incubated in anoxic media at pH 6.4 until pCa of < or = 5, intracellular pH (pHi) of 6.5, and cytosolic [Na+] of 50 mM were reached. On reoxygenation, medium pH was changed to 7.4 to activate Na+/H+ exchange. In one group, 20 microM HOE-694, an inhibitor of Na+/H+ exchange, was added. With or without HOE-694, cytosolic Ca2+ and Na+ returned to control levels within 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 0 publications
3
69
1
1
Order By: Relevance
“…More recent studies have shown that intracellular Na ϩ also rises during ischemia, and that this rise is at least partially dependent on Na ϩ -H ϩ exchange. 20 -22 If NHE1 activity is genetically ablated or inhibited during ischemia, then this should lead to both a more rapid acidification, which reduces contractile activity, 24,46 and a reduction in the amount of Na ϩ to be extruded by the Na ϩ ,K ϩ -ATPase. This would be expected to reduce not only the consumption of ATP during ischemia, but also hypercontracture-induced injury and subsequent no reflow ischemia during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have shown that intracellular Na ϩ also rises during ischemia, and that this rise is at least partially dependent on Na ϩ -H ϩ exchange. 20 -22 If NHE1 activity is genetically ablated or inhibited during ischemia, then this should lead to both a more rapid acidification, which reduces contractile activity, 24,46 and a reduction in the amount of Na ϩ to be extruded by the Na ϩ ,K ϩ -ATPase. This would be expected to reduce not only the consumption of ATP during ischemia, but also hypercontracture-induced injury and subsequent no reflow ischemia during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…3,19 There is evidence that the reduction in cytosolic Na ϩ reduces Ca 2ϩ overload and subsequent hypercontracture that occurs via inhibition or reversal of the Na ϩ -Ca 2ϩ exchanger, 3,20 -22 and that hypercontracture is further reduced by the continuing cytosolic acidification. [23][24][25] Despite experimental support for this mechanism, amiloride and related compounds also affect other Na ϩ transport proteins, including Na ϩ channels 26 and the Na ϩ -Ca 2ϩ exchanger. 27 Although it is unlikely that a significant portion of the cardioprotective effects of NHE inhibitors might be due to interactions with receptors other than NHE1, this possibility has not been rigorously excluded.…”
mentioning
confidence: 99%
“…6,10,23 A decrease in Na ϩ and Ca 2ϩ overload was demonstrated during 20 minutes of ischemia with NMR spectroscopy 7 or 45 Ca 2ϩ using the nonspecific Na ϩ /H ϩ exchange inhibitor amiloride in isolated hearts. 5 Pretreatment with HOE694, a selective, but less potent, Na ϩ /H ϩ exchange inhibitor compared with HOE642, improved cardiac output in the isolated working heart after 20 minutes of global ischemia.…”
Section: ؉ Overload and Ph I On Reperfusionmentioning
confidence: 99%
“…To measure cytosolic Ca¥, Na¤ and H¤ concentrations, cardiomyocytes were loaded at 35°C with fura_2, SBFI or BCECF, respectively (Molecular Probes) as previously described (Ladilov et al 1995). For loading, cells attached to glass coverslips were incubated for 30 min in medium 199 with the acetoxymethyl ester of fura_2 (2.5 ìÒ), or the acetoxymethyl ester of SBFI (10 ìÒ) or BCECF (1.5 ìÒ).…”
Section: Measurement Of Intracellular Ph and Cytosolic Ca¥ And Na¤ Comentioning
confidence: 99%
“…The lack of effect of HOE642 on hypercontracture induced by reoxygenation is in agreement with its lack of effect on intracellular Ca¥ rise secondary to rigor contracture. On the other hand, the maintenance of an acidotic pH during the first few minutes of reoxygenation has been shown to attenuate transient Ca¥ oscillations and to protect cardiomyocytes against reoxygenation-induced hypercontracture (Bond et al 1991Harper et al 1993;Ladilov et al 1995).…”
Section: Protective Effect Against Rigormentioning
confidence: 99%